2014
DOI: 10.1161/circoutcomes.113.000309
|View full text |Cite
|
Sign up to set email alerts
|

Do the Benefits of Participation in a Hypertension Self-Management Trial Persist After Patients Resume Usual Care?

Abstract: Interventions that combine self-management (SM) support and individualized medical management theoretically represent a potentially sustainable intervention for patients with hypertension if they retain and apply skills learned in such interventions after returning to usual care. The longer-term clinical and economic benefits of SM interventions remain largely untested because only 5 prior studies tracked clinical outcomes after completion of SM trials in patients with hypertension. Results from the United Kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
91
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(94 citation statements)
references
References 21 publications
1
91
0
Order By: Relevance
“…However, we recently evaluated clinical benefits of calls similar to those in the TDM Trial and home BP monitoring after the trial concluded. The positive effect of the intervention, which did not include titration of resource intensity, was sustained 18 months following study conclusion 50 Finally, we were not able to maintain our original goal of only including patients who had uncontrolled SBP at baseline. In the final sample, 23.4% of patients had blood pressure under control based on measurements collected at the baseline study visit.…”
Section: 0 Discussionmentioning
confidence: 93%
“…However, we recently evaluated clinical benefits of calls similar to those in the TDM Trial and home BP monitoring after the trial concluded. The positive effect of the intervention, which did not include titration of resource intensity, was sustained 18 months following study conclusion 50 Finally, we were not able to maintain our original goal of only including patients who had uncontrolled SBP at baseline. In the final sample, 23.4% of patients had blood pressure under control based on measurements collected at the baseline study visit.…”
Section: 0 Discussionmentioning
confidence: 93%
“…The study by Maciejewski et al 12 provides further evidence supporting this approach. The Hypertension Intervention Nurse Telemedicine Study (HINTS) was a randomized trial of patients who received care at Durham Veterans Affairs Medical Center primary care clinics.…”
mentioning
confidence: 82%
“…13 This report by Maciejewski et. al 12 adds to the growing evidence that HSM is safe and effective. Indeed, HSM is being implemented in integrated and capitated healthcare systems because it improves BP control and patient satisfaction while preserving office visits for patients who need an in-person assessment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to the usual care, the patients who had been randomized on the combined intervention, had had a great improvement in blood pressure control. The conclusions made, are that the behavioral changes and medicaments can generate improvements in systolic blood pressure, which have been kept 18 months after the intervention was finished (Maciejewski ML., et al, 2014). The patients with high blood pressure frequently do not succeed in fulfilling the goals of treatmenta state defined as an "uncontrolled" hypertension.…”
mentioning
confidence: 99%